(untitled) (Journal of Management and Social Sciences, 2026)
In Nigeria today, the phenomenon of migration, particularly the Japa trend, which means to escape or flee from danger or unpleasant economic situations has now become more prominent. Japa, in the context of migration, suggests that Nigeria is not habitable and that emigration from Nigeria is an escape from misery and economic hardship. The implications of this migration trend are far-reaching and pose significant challenges to Nigeria’s socio-economic fabric. This study explores the socio-economic realities that may shape the Japa mentality among Nigerian youths with a specific focus on undergraduates at the University of Ilorin, Kwara state. Using a survey research design, data were collected from 512 undergraduate male and female at all levels selected from various faculties within the University of Ilorin. The study tested four hypotheses examining whether low-income orientation, perception of infrastructural development, perceived insecurity, and perceived lack of job opportunities significantly predict migration mentality among undergraduates. Simple regression analysis was employed to examine the relationship between these socio-economic realities and the desire to migrate. Key findings revealed significant relationship between low-income orientation, perception of infrastructural development, perceived insecurity, and perceived lack of job opportunities with the desire to migrate. The study highlights how prevailing socio-economic conditions in Nigeria influence youths’ aspirations to emigrate in search of perceived better prospects. The study then recommends for youth entrepreneurship and skill development as sustainable alternatives to reduce migration pressure and potential brain drain. Keywords Youths migration, socio-economic, Japa mentality, income, insecurities. brain drain